Survey on Enhancing Privacy Data Sharing Between Multi-Owners in Cloud for Dynamic Groups - Balaji, A.; Lokesh, M.; Sakthivel, M.; Anbumani, P. (Asian Journal of Engineering and Applied Technology, 2014)
With the character of low maintenance, cloud computing provides an economical and efficient solution for sharing group resource among cloud users. Unfortunately, sharing data in a multi-owner manner while preserving data and identity privacy from an untrusted cloud is still a challenging issue, due to the frequent change of the membership. In this paper, we propose a secure multiowner data sharing scheme, named Mona, for dynamic groups in the cloud. By leveraging group signature and dynamic broadcast encryption techniques, any cloud user can anonymously share data with others. Meanwhile, the storage overhead and encryption computation cost of our scheme are independent with the number of revoked users.